Enhancing University Students’ Functional Fitness by Applying Health Programs Based on Individual Student Heart Rate Monitoring Data - Otaraly, Svetlana; Alikey, Aibek; Sabyrbek, Zhanna; Poteliūnienė, Sniegina (Pedagogika, 2023)
The purpose of this work was to assess the impact on the students’ functional fitness of a one academic year student health-enhancing program based on equipping students with theoretical and methodological knowledge which allows them to analyze the dynamics of their own functional state and interpret digital feedback received from heart rate monitors. Studies have proven that receiving timely feedback of heart rate during the implementation of the training program, is a promising direction to enhance students functional fitness. The obtained research data can help to better understand how providing digital feedback during exercise can help improve student health and self-management skills that are important for students when planning independent physical activity programs.